Effect of the Secondary Rutile Phase in Single‐Step Synthesized Carbon‐Coated Anatase TiO2 Nanoparticles as Lithium‐Ion Anode Material. Issue 4 (24th February 2021) - Birrozzi, Adele; Belchi, Raphaelle; Bouclé, Johann; Geiger, Dorin; Kaiser, Ute; Passerini, Stefano; Herlin-Boime, Nathalie; Bresser, Dominic
Abstract : TiO2 has been investigated as an alternative anode material candidate for lithium‐ion batteries for several years now due to its advantageous safety and rate capability in combination with its nontoxicity and abundance. Herein, the synthesis via laser pyrolysis is reported, which allows the single‐step, industrial‐scale realization of carbon‐coated TiO2 nanoparticles. The modification of the synthesis parameters enables the variation of the rutile‐to‐anatase phase ratio. Following comprehensive physicochemical and electrochemical characterization, both the higher and lower rutile‐to‐anatase ratios show very stable cycling in lithium battery half cells, whereas the extended presence of the rutile phase limits the achievable specific capacity and lowers the apparent lithium‐ion diffusion coefficient, which leads to relatively lower capacities at elevated current densities. Abstract : An industrial‐scale method is used to synthesize carbon‐coated TiO2 nanoparticles, derived in one single step. Depending on the C2 H4 sensitizer flow rate and resulting changes in the reaction temperature, more or less of the rutile phase is obtained in addition to the anatase phase. The less of the rutile phase, the higher the reversible capacity and the faster the apparent Li + diffusion.